ALIRAN PEMIKIRAN POLITIK ISLAM INDONESIA; MUHAMMDIYAH DAN NU VS FPI DAN HTI - Imam Ghozali (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2020)
The successful role of Muhammadiyah and Nahdlatul Ulama (NU) in realizing the independence of the Republic of Indonesia on 17 August 1945 was a form of political compromise between religious and nationalist groups.The political choice of both Islamic Non Government Organizations is a political ijtihad able to unite a form of the unitary State of the Republic of Indonesia (NKRI) with Pancasila ideology. After the birth of the Reformation Era in 1998, emerged new Islamic organizations namely the Islamic Defenders Front (Front Pembela Islam/FPI) and Hizbut Tahrir Indonesia (HTI). Both rejected the NKRI and the Pancasila ideology. According to them, the ideology of Pancasila and the state system does not reflect the teachings of Islamic Shari'ah. They conduct political movements in creating a system of Islamic politics in the form of the caliphate Islamiyah or sharia NKRI. The distinction of political commentary on the ideology and the system of governance is a mirror of the diverse Islamic political traditions in the Islamic sharia. Therefore, this research becomes important to do the political reality of Islam both textual and contextual about the Islamic teachings about the political system and the purpose of Islamic politics itself in realizing human benefits.